Agentic AI: A Game-Changer in Cybersecurity Defense - Mathew, Alex; Jackson, Emma; Tobesman, Audrey (Science and Technology: Developments and Applications Vol. 7, 2025)
Rising aggressive cyber threat development coupled with advanced threat methods demands a complete defense system transformation against cyber-attacks. This research examines Agentic Artificial Intelligence (AAI) as a cutting-edge cybersecurity defense. Practical evidence reveals that AAI systems enhance cybersecurity operations by learning independently as decision-making platforms. AI-based Agentic Algorithms identify and eliminate APTs 94% faster, decrease false alarms 78%, and respond 65% faster than traditional cybersecurity systems. Distributed collaborative agents allowed faster threat data exchange and coordinated responses than networks. Research implies AAI will shift cybersecurity models from defensive to predictive, prioritizing system integrity and morality.